METHODS FOR STUDYING THE LOCALIZATION OF MITOCHONDRIAL COMPLEXES III AND IV BY IMMUNOFLUORESCENT AND IMMUNOGOLD MICROSCOPY - Golić, Igor; Aleksić, Marija; Lazarević, Anita; Bogdanović, Maja; Jonić, Slavica; Korać, Aleksandra (Archives of Biological Sciences, 2016)
The localization of proteins within a cell is very important for studying protein colocalization and subsequently understanding protein-protein interactions at the subcellular level. Using mitochondrial protein localization as a model, we established methods to study the localization of electron transport chain complexes (ETCCs), specifically complexes III and IV, in brown adipose tissue (BAT) and mitochondria. Immunofluorescent and immunogold techniques were applied to BAT paraffin sections and thin Araldite sections of mitochondria-enriched fractions, respectively. Microscopic analysis clearly showed mitochondrial localization of complexes III and IV, as well their colocalization. In addition, 10 and 20 nm gold particles were capable of identifying the localization of complexes within mitochondrial cristae. The methods described in this study may be a beneficial addition to currently utilized methods for accurately identifying the localization of ETCCs, their colocalization with other proteins and their distribution inside the cell and cellular compartments. Lastly, this method can also be used to study the molecular architecture of BAT mitochondria by analyzing fixed and postfixed thin plastic sections with electron microscopy (EM). DOI: 10.2298/ABS150618061G Key words: mitochondria; immunofluorescence; immunogold; localization; brown adipose tissue Received: June 18, 2015; Revised: March 2, 2016; Accepted: March 3, 2016; Published online: July 27, 2016 How to cite this article: Golić I, Aleksić M, Lazarević A, Bogdanović M, Jonić S, Korać A. Methods for studying the localization of mitochondrial complexes III and IV by immunofluorescent and immunogold microscopy. Arch Biol Sci. 2016;68(4):767-72.